ISLAM PROGRESIF VERSI ABDULLAH SAEED (Ikhtiar Menghadapi Problem Keagamaan Kontemporer) - Fathurrosyid . (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2015)
This article dissects the Abdullah Saeed’s notion on Progressive Islam. According to him, progressive Moslem is someone or a group that believes that the socio-religious changes in the contemporary era will not find a solution if the old paradigm of the methodology in the form of devices, without the integrative-interconnective process performed with contemporary scientific disciplines. Therefore, there is a substantive difference between the contemporary problems and the classical problems. In this regard, Saeed offers seven methodologies reinterpret religious texts. First, give attention to the context and dynamics of the socio-historical. Second, realize that there are some topics that are not covered by the Qur because the time has not arrived at the time of the decline. Third, realize that every reading of the scriptures should be guided by the principles of compassion, fairness and honesty. Fourth, know that the Qur recognize a hierarchy of values. Fifth, knowing that it is allowed to move from one concrete example of the generalization. Sixth, should be careful in using other texts of the classical tradition, especially with regard to its authenticity. Seventh, the main focus on the needs of contemporary Moslems.Copyright (c) 2016 by Al-Ihkam. All right reservedDOI: 10.19105/al-ihkam.v10i2.722